(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Construction industry is one of the major sector, which fulfill the basic need of human being i.e. shelter or building infrastructure. In public sector construction industry builds structures like road, dam, bridges, health care centres etc. The building materials are being the backbone of construction activities, are in much demand according to the need in various activities. River sand is one the major building material in construction practice. For various activities of construction, river sand is employed in different forms .Some of the important activities of construction work are masonry mortar, concrete production, plastering works, road construction and many more. The demand for river sand has increased by many folds from last decade due to rapid growth of construction activities. Conventional sources of natural sand are rivers, in which fine aggregates are formed over a period of time by modification of rock particles physically and chemically. The mining of river sand in both legal and illegal forms has led to its scarcity and which produced ill effects on natural sources of fine aggregate. River sand is a non-renewable material hence need to be conserved for the future, there a need for alternatives which will replace the use fine aggregates partially or by full amount. Many alternative materials were analysed to know their properties so as to replace them in various construction works as natural sand. M-sand (manufactured sand) from aggregate manufacturing plant, slag sand (waste produced from steel industry), Construction Demolition waste (waste generated after demolition of buildings) are bi-products of their respective industries. All these alternatives were considered to be waste product and were dumped in landfills. The properties of these wastes are similar to that of fine aggregate, which is confirmed from literature studies. Many of research programmes on alternatives have recommended to use the alternatives as fine aggregate in a fixed percentage of replacement. Since these alternative materials can be obtained in less cost or can be processed, will replace the fine aggregate economically. Use of such alternatives is an eco- friendly practice because of reduction in transport for landfills, hence reducing the CO2 emission. Alternatives will help to reduce the landfill problems in an effective manner. Use of such alternatives as replacement to fine aggregates is a sustainable approach. Hence use of alternatives should be encouraged and recommended by government. Replacing these alternatives in construction activities, is a best way to conserve the natural sources of river sand. In the present study an attempt is made to understand the properties of above mentioned alternatives to river sand as masonry mortar. Strength behaviour of brick masonry specimens made with alternatives is examined i.e. compression, tensile and flexural behaviour of brick masonry. Based on the experimental results, best suitable alternative is recommended as an approach towards sustainability.